Critical Pedagogy and Ta'dib: Towards an Emancipatory-Islamic Education Paradigm - Ruslan Ruslan; Luthfiyah Luthfiyah (Journal of Education and Teacher Training Innovation, 2026)
This study examines the possibility of integrating Paulo Freire’s critical pedagogy and Syed Muhammad Naquib al-Attas’ concept of ta'dib to formulate a new paradigm of Islamic-emancipatory education. Employing a qualitative library research design, the study analyzes primary texts, including Freire’s Pedagogy of the Oppressed and Al-Attas’ major works on Islamic education, complemented by relevant scholarly literature. Data were collected through document analysis and examined using Gadamerian hermeneutic interpretation, comparative analysis, and conceptual synthesis. The analytical process involved identifying the philosophical foundations, educational objectives, epistemological assumptions, and pedagogical implications of both frameworks, followed by the construction of an integrative theoretical model. The findings reveal that Freire’s critical pedagogy emphasizes liberation through critical consciousness, dialogical engagement, and transformative praxis, whereas Al-Attas’ concept of ta'dib focuses on moral discipline, recognition of the hierarchy of knowledge, and the cultivation of adab grounded in the Islamic worldview. Despite their differing epistemological foundations, both perspectives converge in their critique of dehumanizing educational practices and their commitment to human transformation. The novelty of this study lies in the formulation of an Islamic-emancipatory educational paradigm that systematically integrates Freirean critical consciousness with the ethical-spiritual framework of ta'dib. This synthesis offers a theoretical alternative to the dichotomy between secular emancipatory education and traditional Islamic education by positioning education as a process of intellectual liberation, moral refinement, and holistic human development. The proposed paradigm contributes to contemporary debates on Islamic educational reform by providing a framework that is simultaneously critical, ethical, and transformative.